2019
DOI: 10.3390/ijms20174109
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Necrosis in Human Macrophage Cell Lines by Corynebacterium diphtheriae and Corynebacterium ulcerans Strains Isolated from Fatal Cases of Systemic Infections

Abstract: When infecting a human host, Corynebacterium diphtheriae and Corynebacterium ulcerans are able to impair macrophage maturation and induce cell death. However, the underlying molecular mechanisms are not well understood. As a framework for this project, a combination of fluorescence microscopy, cytotoxicity assays, live cell imaging, and fluorescence-activated cell sorting was applied to understand the pathogenicity of two Corynebacterium strains isolated from fatal cases of systemic infections. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…The data sets presented here support and extend results on the interaction of Corynebacterium species; i.e. C. diphtheriae , C. glutamicum and C. ulcerans , with different phagocytic cells published previously [812]. Limitations of the data sets are (i) the use of only one strain per species applied, (ii) the analysis of only one human macrophage-like cell line and (iii) the use of only one MOI in the infection experiments.…”
Section: Limitationssupporting
confidence: 89%
See 2 more Smart Citations
“…The data sets presented here support and extend results on the interaction of Corynebacterium species; i.e. C. diphtheriae , C. glutamicum and C. ulcerans , with different phagocytic cells published previously [812]. Limitations of the data sets are (i) the use of only one strain per species applied, (ii) the analysis of only one human macrophage-like cell line and (iii) the use of only one MOI in the infection experiments.…”
Section: Limitationssupporting
confidence: 89%
“…Recent publications showed that C. diphtheriae as well as C. ulcerans may interfere with phagolysosome maturation in murine and human macrophages after phagocytosis [811]. Most recently, a study combining of fluorescence microscopy, cytotoxicity assays and fluorescence-activated cell sorting revealed that these pathogenic corynebacteria induce necroptosis in human phagocytic cell lines [12]. It was suggested that survival in macrophages and subsequent necrotic lysis of cells may be mechanisms for dissemination of C. diphtheriae and C. ulcerans within the host and support colonization of host tissues far distant from the infection site.…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…HC04 was isolated from a catheter of a 7-year-old girl that developed complications including arthritis, myositis, and peripheral and central nervous system emboli, as well as a microaneurysm with brain hemorrhage, and died due to septic shock caused by endocarditis [ 80 , 81 ]. Infection of THP-1 cells with C. diphtheriae HC04 resulted in condensation of DNA in macrophage nuclei and induced cell lysis, which are clear signs of necrosis [ 82 ]. Live cell imaging experiments revealed that these detrimental effects on macrophages are due to bacterial endocytosis and replication within the host cells.…”
Section: C Diphtheriae -Induced Apoptosis and Necrosismentioning
confidence: 99%
“…Reviews submitted summarize our current knowledge on important pathogens such as Corynebacterium diphtheriae [ 7 ], Staphylococcus aureus [ 8 , 9 ], Legionella species [ 10 ] and Neisseria meningitidis [ 11 ], while research articles highlight specific aspects of host–pathogen interaction. Different mycobacterial pathogens [ 12 , 13 ], Corynebacterium species [ 14 , 15 ], Helicobacter pylori [ 16 ], Mycoplasma fermentans [ 17 ], rickettsiae [ 18 ] and S. enterica [ 19 ] were studied in respect to their interaction with human cell lines. In addition to other human pathogens [ 20 , 21 , 22 , 23 , 24 ], animal- [ 25 , 26 ] and plant-pathogenic bacteria [ 27 , 28 , 29 , 30 ] were investigated.…”
mentioning
confidence: 99%